School bullying and bare life: Challenging the state of exception. Issue 14 (6th December 2019) - Horton, Paul
Abstract: Despite a vast amount of research into school bullying and the widespread implementation of anti-bullying policies and programs, large numbers of students continue to report that they are routinely subjected to bullying by their peers. In this theoretical article, I argue that part of the problem is that there has been a lack of critical discussion of the theoretical foundations upon which such studies are based. Drawing on recent theoretical contributions within the field of school bullying, the work of anthropologist James C. Scott, and the work of philosophers Michel Foucault and Giorgio Agamben, I take particular issue with the notion of power that has long been a foundational pillar of bullying definitions. Utilizing a Foucauldian understanding of power, I argue that rather than focusing on the power imbalance involved in bullying relations, focus instead needs to shift onto the role that bullying plays in power relations. Reimagining Agamben's figure of homo sacer as a victim of school bullying, I consider the ways in which some individuals are reduced to bare life and forced into a state of exception whereby social laws are no longer deemed applicable. The article concludes with a discussion of how this state of exception might be challenged.